A systematic review of the effect of different crimping techniques in stapes surgery for otosclerosis. (29th August 2015) - Wegner, Inge; Swartz, Justin E.; Bance, Manohar L.; Grolman, Wilko
Abstract : Objectives/Hypothesis: To evaluate the effect of crimping techniques in stapes surgery for otosclerosis patients measured by hearing outcomes on pure‐tone audiometry. Data Sources: PubMed, EMBASE, and the Cochrane Library. Methods: A systematic search was conducted. Studies comparing the effect of different crimping methods on pure‐tone audiometric results in patients undergoing stapes surgery for otosclerosis were included. Relevance and risk of bias were assessed. Absolute risks and risk differences, means and mean differences, and 95% confidence intervals were extracted or calculated for the primary and secondary outcomes, which were air‐bone gap closure to 10 dB or less, mean postoperative air‐bone gap, and postoperative sensorineural hearing loss. Results: Twenty‐two studies with moderate or high risk of bias were included for data extraction. Air‐bone gap closure to 10 dB or less was assessed in 17 studies and mean postoperative air‐bone gap in 20 studies. The hearing outcomes did not consistently favor one crimping method. However, the differences that were statistically significant were consistently in favor of heat crimping over manual and no crimping (difference in air‐bone gap closure to 10 dB or less ranged between 22% and 42% in these studies and difference in mean postoperative air‐bone gap between 2.8 dB and 7.4 dB) and in favor of manual crimping over no crimping (30% difference in air‐bone gap closure to 10 dB or less and difference in mean postoperative air‐bone gap between 2.6 dB and 6.0 dB). Conclusion: Moderate to high risk of bias and inconsistent results characterize the current evidence. Laryngoscope, 126:1207–1217, 2016